Parent’s Perspective on Continuity of Care in the Maternity Care and Child Health Services Continuum: A Qualitative Systematic Review - Anne C. M. Hermans; Silke Boertien; Lauri M. M. van den Berg; Ank de Jonge; Danielle E. M. C. Jansen; Arie Franx; Jacoba van der Kooy; Marlou L. A. de Kroon (International Journal of Integrated Care)
Introduction: While the World Health Organization (WHO) advocates organizing maternity care and preventive child healthcare (PCHC) as people-centred, integrated healthcare services, globally these services are often established separately, causing discontinuity of care. Our aim is to synthesize the evidence concerning what impacts parents’ experience of continuity of care, and how to promote it. Methods: Qualitative systematic review. Embase, Medline, Web of Science, Cochrane, CINAHL and Google Scholar were searched for studies on parents’ perspectives on integrated care. Helpful practices and issues regarding continuity of care were identified. Results: We found that parents valued easily accessible, tailored, family-centred care that is a display of interprofessional collaboration and is geared towards supporting and empowering parents. Discussion: Study strengths are its qualitative nature, allowing for in-depth patient views and experiences, and the multidisciplinary research team, which ensured a multidimensional view of the issue. Conclusion: Ideally, (a) parents enter the postnatal period well-prepared, and well-informed about self-care, PCHC and possible postnatal carepathways, (b) number of caretransfers is limited, (c) by overlapping maternity care and PCHC, parents are provided with an opportunity to maintain meaningful relationships with their care providers, and (d) information is consistent, family-centred, and tailored.